Pertumbuhan Bakteri Anaerobic Ammonia Oxidation (Anammox) Pada Salinitas 2 dan 9 Persen - Wijanarka Wijanarka; Sudarno Sudarno; Novi A. Pratama (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
When ammonia in waste water is lost inappropriately, it will raise an adverse environmental effect for the aquatic cycle. Anammox, anaerobic ammonia oxidation, is a novel process in which nitrite is used as an electron acceptor in the conversion of ammonium to nitrogen gas. The anammox process removes ammonium in the autrotrophic system by leaving little biomass. This study aims to analyze the effect of salinity on the growth of anammox bacteria. The samples used were from the brackish water sediments of the East Flood Canal River of Semarang. The isolation was done by gram staining and the bacteria were inoculated on media with different salinity concentration and the growth was measured using spectrophotometer. The results showed that anammox bacteria had a higher growth rate of 3% (control) when it was grown on a medium with a concentration of 9%. Anammox bacteria grown on anammox selective media showed that the bacteria were able to adapt to environments with different salinity concentrations of 2% and 9%. Key words: anammox, ammonium, nitrogen, anammox bacteria.